Compatibility between Pseudomonas fluorescens and Trichoderma harzianum in disease control of Fusarium tomato wilt under greenhouse condition . - Baghdad Science Journal (مجلة بغداد للعلوم)
This study was conducted to evaluate the efficacy of 6 isolates of Pseudomonas fluorescens and Trichoderma harzianum and there combination against Fusarium tomato wilt disease caused by Fusarium oxysporum F.sp. Lycopersisi under green house condition .The isolates of bacteria (B3) and Trichoderma (T1) were found to be highly effective in reducing the disease incidence to 13.3% , 21% respectively , compared to control treatment (40%).Furthermore, disease severity was reduced to 28 and 30% respectively in comparison to control (90%) .Colonization of the roots (cfu /g fresh root weight )by the two isolates whether alon or together was extremely high . The combination treatment had a high ability in reducing disease incidenece and severity to 10,3 , 16% respectively compared to control (36.3% , 88 % respectively), and highly effective in increasing some growth parameters .